PELATIHAN PERPAJAKAN UNTUK UMKM DI MAJELIS DA’WAH AL’ADNI - Zulfitra, Zulfitra; Ganar, Yulian Bayu; Krisyanto, Edy; Mubarok, Ali; Dinantara, Mohamad Duddy (LPPM Universitas Pamulang, 2020)
This Community Service aims to introduce taxes to the MSMEs in the Da'wah Al-Adni Assembly. Issues raised regarding taxation for MSMEs. Methods The implementation method of this service is carried out in several activities, namely (a). The Preparation Phase includes: (1). Initial survey (2) Consolidation and determination of target locations, (3). Preparation of training materials / materials. The results of this activity are very useful for Majlis Da'wah Al-Adni in the formation of MSMEs and add insight and knowledge about MSME taxes.